Urban Land Use Dynamics of Bhopal: Reflections from Development Plans - Singh, Arun Kr. (National Geographical Journal of India, 2022)
Land use is defined as spatial aspects of the types of human activities on the piece of land to serve the human needs. Urban land use deals with the pattern of spatial distribution of the city's functions. Different theories have been put forward to explain the urban land use pattern which is a reflection of the anthropogenic transformation and dynamicity of the city and is conditioned, controlled and shaped by various phases of histogenetic evolution. Broadly, urban land use is categorized as developed and undeveloped areas. Further developed areas are put to different categories of land uses and with the passage of time as population increases, economy diversifics and city expands, a change in land use pattern takes place. Bhopal, is taken as the case study to examine the changing land use pattern since its inception as a capital city. Two developments firstly declaring Bhopal as capital city of Madhya Pradesh and secondly setting up of public sector undertaking (BHEL) in mid fifties led to spurt of urban population, shrinking urban amenities and leading to the poor living conditions. To handle the situation and remove the hardships an interim development plan for the city was prepared in early sixties.BDP-2005 aimed at the balanced urban and regional development in integrated manner and envisions Bhopal as a multi-functional city which is not only an eco friendly city but also a centre for technology transfer and a cultural and heritage centre. The paper firstly attempts to examine and analyse the changing urban land use in the context of changing functional base and level of implementation of two development plans and secondly examine the proposals of BDP 2021 which laid the ground for withdrawal of the Plan